Antioxidant Properties of Four Commonly Consumed Popular Italian Dishes - Alessandra Durazzo; Massimo Lucarini; Antonello Santini; Emanuela Camilli; Paolo Gabrielli; Stefania Marconi; Silvia Lisciani; Altero Aguzzi; Loretta Gambelli; Ettore Novellino; Luisa Marletta (Molecules, 2019)
Four popular dishes belonging to Italian cuisine and widely consumed in the country were experimentally prepared in a dedicated lab-kitchen following a validated and standardized protocol. This study provides their antioxidant properties evaluating the contribution of extractable and non-extractable bioactive compounds, and identifying the assessment of interactions between their natural active compounds and the food matrix. Ferric reducing antioxidant power (FRAP) values in aqueous-organic extract ranged from the highest antioxidant activity in torta di mele (10.72 µmol/g d.m.) to that in besciamella (2.47 µmol/g d.m.); in residue, pasta alla carbonara reached the highest value (73.83 µmol/g d.m.) following by that in pasta alla amatriciana (68.64 µmol/g d.m.). Total polyphenol content (TPC) ranged in aqueous-organic extracts between 36.50 and 64.28 mg/100 g d.m. and in residue from 425.84 to 1747.35 mg/100 g d.m. Our findings may contribute to the updating of the Italian Food Composition Database, by providing for the first time a value for the antioxidant properties. This could contribute to encourage the consumption of recipes rich in key nutrients and bioactive molecules. This information is useful and important for determining the association between diet and a healthy status.